تصورات الصحة و المرض لدى الطلبة الجامعيين - بن فرج الله, بختة (جامعة الوادي - University of Eloued, 2022)
الملخص: تعتبر الصحة و المرض وجهان لظاهرة واحدة كانت منذ وجدت المجتمعات الإنسانية و مازالت حتى وقتنا الحاضر من الشواغل الأساسيـة التي تشغل الناس أفراداً و جماعات ، حيث تختلف المعاني الاجتماعية لآرائهم و مواقفهم اتجاه كل من الصحة و المرض و في ها السياق جاءت هذه الورقة البحثية تتطرق إلى موضوع التصورات حول الصحة و المرض عند فئة تعتبر من الفئات التي تشكل الركائز الأساسية للمجتمع لم تحمله من مميزات و خصائص تجعلها تلعب دورا أساسيا في بناء المجتمع و تطوره و هي فئة الطلبة الجامعيين ومن اجل تحقيق أهداف البحث و الكشف عن هذه التصورات تم القيام بدراسة ميدانية على عينة قصديه من الطلبة بجامعة الوادي بإتباع المنهج الوصفي التحليلي، كما تعد هذه الدراسة بمثابـة فرصـة تسمح بفهم المواقف اتجاه الصحـة و المرض. Abstract: Health and disease are two sides of a single phenomenon that has existed since human societies existed and is still one of the main concerns that occupy people, individuals and groups, as the social meanings of their opinions and attitudes towards health and disease differ, and in this context, this research paper came to address The subject of perceptions about health and disease in a group that is considered one of the groups that constitute the basic pillars of society did not bear the characteristics and characteristics that make them play a key role in building and developing society, which is the category of university students. On an intentional sample of students at the University of Eloued, following the descriptive analytical approach, this study is also an opportunity to understand attitudes towards health and disease.
دراسة ميدانية لعينة من الطلبة بجامعة الوادي
مقال
Keywords: صحة؛ مرض؛ تصور الصحة ؛ تصور المرض؛ طالب الجامعي; health; disease; perception of health; perception of disease; university student